2012
DOI: 10.1002/chem.201200511
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Möbius Topologies in [26]‐ and [28]Hexaphyrins

Abstract: Recently, hexaphyrins have emerged as a promising class of π-conjugated molecules that display a range of interesting electronic, optical, and conformational properties, including the formation of stable Möbius aromatic systems. Besides the Möbius topology, hexaphyrins can adopt a variety of conformations with Hückel and twisted Hückel topologies, which can be interconverted under certain conditions. To determine the optimum conditions for viable Möbius topologies, the conformational preferences of [26]- and [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(109 citation statements)
references
References 142 publications
7
101
0
Order By: Relevance
“…We have previously demonstrated that computational chemistry is ap owerful tool in aiding the design of viable Mçbius expanded porphyrins with high aromatic character. [38][39][40][41] Our initial research focusing on metal-free expanded porphyrins varying in ring sizes and oxidation states revealed thatt he conformation of the hexaphyrin macrocycle is clearly dependento n the oxidation state. [38] [26]hexaphyrin 1 strongly prefers aH ückel conformation, planar and highly aromatic, whereas antiaromaticH ückel and aromatic Mçbius conformers coexist in dynamic equilibrium for [28]hexaphyrin 2.H erein, the metalation effect of d 8 metalso nt he molecular topology of 1 and 2 is scrutinized in detail.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that computational chemistry is ap owerful tool in aiding the design of viable Mçbius expanded porphyrins with high aromatic character. [38][39][40][41] Our initial research focusing on metal-free expanded porphyrins varying in ring sizes and oxidation states revealed thatt he conformation of the hexaphyrin macrocycle is clearly dependento n the oxidation state. [38] [26]hexaphyrin 1 strongly prefers aH ückel conformation, planar and highly aromatic, whereas antiaromaticH ückel and aromatic Mçbius conformers coexist in dynamic equilibrium for [28]hexaphyrin 2.H erein, the metalation effect of d 8 metalso nt he molecular topology of 1 and 2 is scrutinized in detail.…”
Section: Resultsmentioning
confidence: 99%
“…As additional geometrical descriptors, we computed the average dihedral angle between neighboring pyrrole rings (Φ p ) as a measure of the torsional ring strain [ 37 ] and the π-conjugation index ( Π ) to quantify the extent of the effective overlap of neighboring p orbitals [ 1 ]. Π equals 1 for a completely planar system, it is positive for any Hückel (double-sided) conformation and negative for any Möbius (single-sided) surface.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In our recent computational research on expanded porphyrins, we have proposed a set of descriptors for measuring the global aromaticity of porphyrinoids based on energetic, structural, magnetic and reactivity criteria [ 37 , 38 , 39 ]. Although some discrepancies exist between the different indices, overall the energetic, reactivity, structural, magnetic and electronic indices nicely agree on the general (anti)aromatic features of these compounds in agreement with the annulene model [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52][53][54] In this sense, it is not unexpected that expanded porphyrins are among the most challenging test beds for aromaticity descriptors. It should be pointed out that several works 20,[55][56][57][58][59][60][61][62] have recently analyzed the aromaticity of expanded porphyrins with different topologies and number of π electrons using various aromaticity indices based on the energetic, magnetic, structural, and reactivity criteria. The last problem to describe the aromaticity of porphyrinoids is the critical role of the selected density functional approximations (DFA) to evaluate geometric, energetic and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%